2009
DOI: 10.1111/j.1741-3729.2009.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Maternal Work Stress, Negative Work‐Family Spillover, and Depressive Symptoms

Abstract: The current study examined associations over an 18-month period between maternal work stressors, negative work-family spillover, and depressive symptoms in a sample of 414 employed mothers with young children living in six predominantly nonmetropolitan counties in the Eastern United States. Results from a one-group mediation model revealed that a less flexible work environment and greater work pressure predicted higher levels of depressive symptoms, and further, that these associations were mediated by percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 31 publications
2
61
0
1
Order By: Relevance
“…The analyses also focused on a limited number of mediating and moderating variables, and investigating other psychological and behavioral variables may shed further light on the complexities of stress spillover among children and adolescents. In light of research suggesting that spillover may partially explain the relationship between work stress and depressive symptoms among adults (Franche et al 2006;Goodman and Crouter 2009), exploring the mediating role that spillover itself plays between academic stress and later well-being may also be a productive avenue for future research.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The analyses also focused on a limited number of mediating and moderating variables, and investigating other psychological and behavioral variables may shed further light on the complexities of stress spillover among children and adolescents. In light of research suggesting that spillover may partially explain the relationship between work stress and depressive symptoms among adults (Franche et al 2006;Goodman and Crouter 2009), exploring the mediating role that spillover itself plays between academic stress and later well-being may also be a productive avenue for future research.…”
Section: Discussionmentioning
confidence: 97%
“…However, perhaps the largest gap in the literature on stress spillover among children and adolescents pertains to factors that may moderate social-academic linkages. There is evidence from the work-family literature that spillover may partially explain the relationship between work stress and depressive symptoms (Franche et al 2006;Goodman and Crouter 2009), suggesting that spillover may have important consequences for later mental health. Assuming that spillover may also have consequences for adolescent wellbeing, investigating moderators is of key importance for understanding the circumstances under which spillover occurs and for identifying individuals who may be more vulnerable to spillover.…”
Section: Introductionmentioning
confidence: 99%
“…Both acute workrelated stressful experiences as well as more stable structural occupational factors contribute to depressive disorders [42]. For example, a longitudinal study of working mothers with young children found that a less flexible work environment and greater work pressure predicted higher levels of depressive symptoms even 18 months later [43]. However, these effects are not observed for everyone [44].…”
Section: Unwinding From Daily Job Stressmentioning
confidence: 96%
“…A US study found that the relationship between job demands (reduced flexibility and work pressure) and depressive symptoms in a large sample of working mothers (n 0 414) was partially mediated by the mothers' views of their job-to-home negative spillover (Goodman & Crouter, 2009). A study by van Hoof et al (2005) with 730 workers from the Dutch police force explored the link between integration-based difficulties and workers' well-being.…”
Section: Conceptual Perspectivesmentioning
confidence: 95%